On safari: a sparkly board book (Alligator Books limited London, 2004)
This vibrant sparkly board book takes young readers on an exciting adventure through the African savannah. With colorful illustrations and playful rhymes, children encounter a variety of animals, from elephants to lions, as they explore their habitats. The interactive elements, including shimmering pages, engage little ones, making it a delightful read-aloud experience that sparks curiosity about wildlife and nature. Perfect for early learners, this book invites imagination and encourages a love for reading.